WATER RELATION, GAS EXCHANGE AND DRY MATTER PRODUCTION OF COCONUT (COCOS NUCIFERA, L.) UNDER UNIRRIGATED AND IRRIGATED CONDITIONS - K.V. Kasturi Bai; V. Rajagopal; D. Balasimha; P. Gopalasudaram (International Coconut Community, 1997)
The response of local West Coast Tall (WCT) and the two hybrids viz., WCT x Chowghat Orange dwarf (COD) and COD x WCT to moisture availability in terms of water relation, gas exchange and dry matter (DM) production was studied. Discernible differences were noticed between the irrigation treatment (viz., irrigated vs unirrigated) with lower stomatal conductance and transpiration rate in the palms with out irrigation. Irrespective of the cultivar of hybrid leaf water potential was also significantly higher in irrigated palms. Net assimilation rate was lower under uniriigated condition. However genotypic or treatment differences were not significant. Annual DM production also vaned markedly between the irrigation treatments. Treatment differences were significant on the reproductive (RDM) rather then vegetative DM (VDM) production. Under the irrigation treatment the hybrids performed better than the local tall However the percentage reduction in the DM production was relatively less in the local WCT cultivar under unirrigated as compared with irrigated condition. The studies clearly highlighted the beneficial effects of irrigation on DM production and yield in coconut and the adaptability of the local WCT variety under limited water supply than the two hybrids.